A Case of Jessner's Lymphocytic Infi ltrate and Cutaneous B-Cell Follicular Lymphoma: Coexistence or Transformation? - Bryan Murphy; Helen Hunter; Jennifer Somerville (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2017)
Jessner's lymphocytic infi ltrate of the skin is a rare, benign cutaneous disorder. Diffi culty arises in differentiating it from cutaneous lymphoma on histology, thus requiring immunophenotying, however the literature lacks reports demonstrating malignant transformation or dual pathology. We present a case of Jessner's lymphocytic infi ltrate who later presented with areas of cutaneous B-cell follicular lymphoma.